Synergistic effect of humic acid and phosphate solubilizing bacteria on rhizospheric functions and phosphorous acquisition in direct-seeded rice (Oryza sativa) - ALI, S K ASRAFUL; DHYANI, VIPIN CHANDRA; KUMARI, ANJALI; PRAJAPATI, SUNIL KUMAR (The Indian Journal of Agricultural Sciences, 2025)
This study was carried out during the rainy (kharif) season of 2022 and 2023 at Govind Ballabh Pant University of Agriculture and Technology, Pantnagar, Uttarakhand to investigate the synergistic effects of humic acid (HA) and phosphate solubilizing bacteria (PSB) under reduced phosphorus fertilisation on root development, microbial activity, and phosphorus acquisition in direct-seeded rice (DSR) (Oryza sativa L.). Experiment was laid out using a factorial randomized block design (FRBD) with 12 treatment combinations. Treatments included three phosphorus levels (control, 50%, and 100%, corresponding to 0, 30, and 60 kg P2O5/ha) and four phosphate solubilizers (control, HA @10 kg/ha, PSB @10 g/kg seed, and HA @10 kg/ha + PSB @10 g/kg seed). Results showed that 100% phosphorus significantly increased root dry weight density (2922 g/m3) and root volume density (6129 cc/m3), representing improvements of 18.4% and 37.4% over the control, respectively. The combined HA + PSB treatment at 50% phosphorus achieved root traits comparable to full phosphorus application, indicating improved phosphorus use efficiency (PUE). PSB populations were highest under HA + PSB (22.67 × 10⁴ CFU/g soil), while acid and alkaline phosphatase activities increased by 11–19% and 10–11% over sole PSB, respectively. Growth parameters and grain yield were also enhanced, with plant height, tillers, and dry matter accumulation increasing by 8.2–15.2% compared to the control. Overall, integrating HA and PSB with 50% phosphorus effectively sustained root growth, microbial populations, phosphatase activity, and grain yield, demonstrating a viable strategy to optimize PUE, reduce fertiliser costs, and maintain rice productivity under DSR systems.